Relative Clause French: An Approach to Syntactic Typology - Nurilam Harianja; Mulyadi (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2022)
This study aims to describe the constituent forms of the French relative clause. The data source of this research is written text, namely the Tendance book. The data analysis method uses the billing method. The result of this research shows that the basic order of clauses in French is of type , namely the verb precedes the object. the object of the preposition is included in the constituent. Nod and Np constituents in the form of pronouns are in front of the verb, the French Relative Clause is not only a delimiter in noun phrases. French has relatively simple pronouns and relatively complex pronouns. The form of the verb that is conjugated will change according to the type (feminine or masculine) or from the angle of form (singular or plural). All relative pronouns in French have their respective functions according to the noun phrase they replace. From the conclusion above, it is clear that every language has its own uniqueness, even though there are similarities or differences.